Earnings management in initial public offerings. - Tan, Chee Keng. (2009)
The purpose of this dissertation is to examine if earnings management is practised in firms seeking listing for the first time. In the first part of this dissertation, I examine the relationship between discretionary accruals at the time of an IPO and subsequent cash flows and net income to determine if the accruals appropriately reflect the future economic activities of the firm. The results show that the discretionary portion of both the working capital accruals and total accruals show an increasing trend from year minus 3 (relative to IPO year) to IPO year (year 0) and are unusually high at the year of IPO. The discretionary accruals could have been caused by the increase in non-cash current assets arising from the discretionary portion of trade receivables, or possibly an underprovision of bad and doubtful debts.